Analysis of the Relationship between Organic Material Content and Sediment Grain Size with Macrozoobentos Abundance in Sungai Selari Village, Bengkalis Regency - Fahira, Adhita Fiky; Mubarak, Mubarak; Tanjung, Afrizal (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
Sungai Selari Village is an area in Riau Province that features a high density of water activities, including a port where many fishing boats are moored and also serves as a transportation route for fishermen seeking fish. This activity can cause water pollution, which leads to the silting of waters through sedimentation. The activity of sediment input into a body of water can cause changes in the ecosystem, including alterations in sediment texture, organic matter content, and the abundance of macrozoobenthos biota. One organism that can be affected by differences in ecosystems is the macrozoobenthos due to its sedentary nature. This study aims to determine the type of sediment, grain size, and organic matter content, as well as their relationship with macrozoobenthos abundance. This research was conducted in March and April 2023, utilizing purposive sampling techniques at four stations in total. The samples taken were sedimentary substrates and macrozoobenthos. The results indicated that the size of the dominating sediment stalk, specifically the mud fraction, ranged from 14.72% to 71.25%. The types of macrozoobenthos found are grouped into two classes, namely Gastropods and bivalves. Individual abundances range from 0.3 - 4.4 ind/m2, with the highest abundance occurring at station 4 and the lowest occurring at station 1. The organic matter content ranges from 9.27- 34.2%. The relationship between organic matter content and macrozoobenthos abundance exhibits a moderate correlation of 0.506. The relationship between sediment grain size and macrozoobenthos abundance shows a fairly close correlation of 0.544